The Effect of Burnout and Turnover Intention on Employee Performance in Banking - Rosaria Angelita; Ika Korika Swasti (International Journal of Economics and Management Sciences, 2025)
This study aims to analyze the effect of burnout and turnover intention on employee performance in banks. Declining performance and high work pressure in the micro banking sector are important reasons for conducting this study. The research uses a quantitative approach with a survey method, involving 42 respondents from the credit, marketing, and teller divisions. Data collection was carried out through the distribution of questionnaires using a 1–5 point Likert scale, which were then analyzed using the Partial Least Squares (PLS) method through the SmartPLS 4 application. The results show that both burnout and turnover intention negatively affect employee performance. This means that as employees experience higher levels of emotional exhaustion and a stronger intention to leave their job, their performance declines. The study highlights the importance of addressing these psychological factors to enhance employee performance. The findings imply that company management should focus on improving the psychological well-being of employees to ensure the stability of organizational performance, reduce turnover, and maintain a productive workforce.